Tratamiento contable de la NIIF 15 para la compañía de construcciones civiles y metálicas CONSTRUME S.A. - Aspiazu Izquierdo, María Lorena (2020)
This research work is prepared based on the country's need to face an unstable economy that forces it to apply International Financial Reporting Standards IFRS to certain sectors, including construction, which is why my research work is entitled Accounting Treatment of IFRS 15 for Compañía de Construcciones Civiles y Metálicas CONSTRUME SA The Company in its Financial Statements does not comply with a correct accounting treatment under the application of IFRS 15 Income from Ordinary Activities from contracts with clients, for which reason there is an incorrect accounting of its income, work progress and advances corresponding to its contracts. , which causes very high differences in certain accounts, tax problems and incorrect financial indicators……………